Mandarin Chinese Picture Dictionary - Yi Ren (Tuttle, 2018)
This Illustrated dictionary present 1,500 key Mandarin Chinese words and sentence that students need to know to pass the AP Chinese Language adn Culture Exam and the Chinese goverment HSK Lecels 1 -3 proficiency exam.